Suppression of Hepatic Epithelial-to-Mesenchymal Transition by Melittin via Blocking of TGFβ/Smad and MAPK-JNK Signaling Pathways - Park, Ji-Hyun (Toxins (Basel), 2017)
Transforming growth factor (TGF)-β1 plays a crucial role in the epithelial-to-mesenchymal transition (EMT) in hepatocytes and hepatic stellate cells (HSC), which contributes to the pathogenesis of liver fibrosis. Melittin (MEL) is a major component of bee venom and is effective in rheumatoid arthritis, pain relief, cancer cell proliferation, fibrosis and immune modulating activity. In this study, we found that MEL inhibits hepatic EMT in vitro and in vivo, regulating the TGFβ/Smad and TGFβ/nonSmad signaling pathways. MEL significantly inhibited TGF-β1-induced expression of EMT markers (E-cadherin reduction and vimentin induction) in vitro. These results were confirmed in CCl(4)-induced liver in vivo. Treatment with MEL almost completely blocked the phosphorylation of Smad2/3, translocation of Smad4 and phosphorylation of JNK in vitro and in vivo. Taken together, these results suggest that MEL suppresses EMT by inhibiting the TGFβ/Smad and TGFβ/nonSmad-c-Jun N-terminal kinase (JNK)/Mitogen-activated protein kinase (MAPK) signaling pathways. These results indicated that MEL possesses potent anti-fibrotic and anti-EMT properties, which may be responsible for its effects on liver diseases.